Adaptive Chemoenzymatic Microreactors Composed of Inorganic Nanoparticles and Bioinspired Intrinsically Disordered Proteins. Issue 21 (15th April 2020) - Capasso Palmiero, Umberto; Küffner, Andreas M.; Krumeich, Frank; Faltova, Lenka; Arosio, Paolo
Abstract: The assembly of protein and inorganic nanoparticles represents an attractive approach to generate composite materials with multiple functions. Herein, we functionalize inorganic nanoparticles with intrinsically disordered protein domains associated with the formation of membraneless compartments in cells. These protein sequences, defined as low complexity domains (LCDs), encode intermolecular interactions that drive highly controlled, dynamic self‐assembly in response to environmental changes. We show that the properties of the LCDs can be transferred to inorganic nanoparticles, inducing controlled phase separation that is dynamic and responsive to ionic strength and pH. Specifically, we hybridize magnetic nanoparticles with multi‐domain proteins consisting of LCD domains and a globular enzyme, generating dynamic protein‐composite compartments that locally confine hybrid chemoenzymatic reactions and respond to external magnetic fields and changes in solution conditions. Abstract : A class of intrinsically disordered proteins plays key roles in highly regulated cellular compartmentalization. Conjugation of these proteins with magnetic nanoparticles generates composite compartments that exhibit multiple functions, coupling reversible self‐assembly in response to pH, ionic strength, and magnetic fields with the ability to locally confine hybrid chemoenzymatic reactions.